PROSPEK PEMANFAATAN TEPUNG JAGUNG UNTUK KUE KERING (COOKIES) - Suarni Suarni (Badan Penelitian dan Pengembangan Pertanian, 2009)
Prospect of maize flour for cookiesCookies is one of the favorite snacks consumed by community. The average consumption of dry cake in the big city and village in Indonesia is 0.40 kg/capita/year. Cookies processing do not need volume development as wet cake and bread, but the cookies have to be crispy, imperishable to water, hard and unbroken easily. This relates with the physiochemical characteristic and functional of maize flour. Maize flour has hard texture, relatively low gluten content (< 1%) with amylograph features processing the cold viscosity (240620 BU). This papers described the results of research relating with the nutrition content, functional characteristic, and the construction of dry cake from maize flour. The cookies made from maize flour have good nutrition quality and adequate processing feature, substitution towards the wheat flour until the level 5080% with the receiving level of highly preference (organoleptic). Supported by the recipe of dry cake that popular in the recent time were using the corn based material for example corn flake, coco chip, corn crispy. This indicated the opportunity of utilizing maize flour corn powder that has already received by the modern community who processing the high prospect to be developed.